KULTUR SEKOLAH DALAM MEWUJUDKAN PENDIDIKAN BERBASIS KEUNGGULAN LOKAL BATIK DI SMA NEGERI 1 SOKARAJA - Abiyoga, Berlian Bima (Spektrum Analisis Kebijakan Pendidikan, 2021)
This research aimed to describe school culture in the realization of Batik local content based education in 1 Sokaraja State Senior High School. The focuses of this study were deep explaination of school culture which was Batik local content based education and how to realize it. This research used descriptive qualitative approach. Data were collected using observation, interview, and documentation. Data analysis was done using interactive analysis model by Miles and Huberman namely data condensation, data presentation, and drawing conclusion. The data were validated using technique and source triangulations. The results of this study indicated that physically and behaviorally 1 Sokaraja State Senior High School has supported the school culture of Batik local content based education. Three basic layers of school culture were assumptions, values, and artifacts. The assumptions of the founders of Batik local content based education at 1 Sokaraja State Senior High School who strongly wanted to elevate the local culture of Banyumas Batik underlie the formation ofÂ  Batik local content based education. The values that applied were the value of cleanliness, the value of discipline, the culture of courtesy, the value of achievement, and the cultivation of local values. Then, the artifacts were in the forms of supporting facilities, efforts, and programs that support the Batik local content based education.Keywords: School Culture, Local Content based Education, Batik